Analysis of problems of accounting reliability provision in clusters - Hlasov, Pavlo (Technology audit and production reserves, 2018)
The object of research is theoretical and practical aspects of the formation of management reporting and the problematic issues of preventing accounting distortions in clusters. The question of assessing the quality of accounting information in particular, the nature and place of accounting information in cluster management, accounting in the management information system of enterprises participating in the cluster, accounting and reporting tools are not sufficiently developed. The order of formation of accounting information and the preparation of management accounting reports in clusters are investigated, and the specifics of the quality of accounting information and the effectiveness of the accounting system are determined. In the process of research methods of generalization, systematization, and system analysis were used. Using these methods, the definition of the concepts «intracorporate management reporting», «unreasonable classification of expenses», and «accounting information» has been proposed. Also the main problems hampering the need to implement and automate a full-fledged management accounting system are grouped that would meet all the challenges and needs of modern business and suggested ways to solve them. Special attention is paid to the formation of information support for solving specific management problems. Despite some progress in the development (in particular, the basic principles of standardization) of accounting and reporting, there are serious problems regarding the adequacy of the methodological foundations of accounting for the current state of the market environment and the needs of users. Accounting systems do not fully ensure the proper quality and reliability of the information they form, which significantly limits the usefulness of this information. In the work, reliable financial statements are analyzed as an important tool for making sound and important management decisions in clusters. The research results will be useful when conducting an audit, including when planning an audit, as the accountant and the head of the company need to take into account the possible presence of distortions in the financial statements. And, on this basis, assess the risk of misstatement of financial statements and take measures to prevent such violations in the future.